ANALISIS TINGKAT PRODUKSI DENGAN METODE TRADISIONAL DALAM MENINGKATKAN KAPASITAS PRODUKSI USAHA TEMPE UWAK HASAN DI KELURAHAN PASAR KOTA GUNUNGSITOLI - Arhanif Syahputra Lase; Jeliswan Berkat Iman Jaya Gea; Eduar Baene; Kurniawan Sarototonafo Zai (Jurnal Publikasi Manajemen Informatika, 2025)
The level of production using traditional methods is a production process activity that is generally used. The success of a business can also be considered as an increase in quantity and quality aimed at achieving success. In this research, the problem is the conditions at the level of consumer and market demand for tempe products. The aim of this research is to determine the level of production using traditional methods, quality control, and the level of production using machine technology in the Uwak Hasan tempe business, Pasar Subdistrict, Gunungsitoli City. This research uses qualitative research. Data collection techniques are observation, documentation and interviews. Data analysis techniques using data reduction, data presentation and drawing conclusions. Based on the research results obtained, it can be concluded that the application of the Uwak Hasan tempeh production process is still not optimal because it still applies the production process using traditional methods which are commonly used, efforts to support the production process in facing the high demand for tempeh products, Uwak Hasan tempeh business carrying out product development, understanding the market situation, customer needs, monitoring and training employees so that the production process runs as expected.